Pengaruh Gaya Kepemimpinan, Human Relations Dan Disiplin Kerja Terhadap Kinerja Pegawai (Pada Dinas Koperasi dan Usaha Mikro Kabupaten Sumenep) - Nova Ismi Haryadi; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstrackThe purpose of this to analyze and explain the influence of leadership style, human relations, and work discipline on employee performance at the Department of Cooperatives and Micro Enterprises Sumenep Regency. The dependent variable in this study is employee performance, there are 3 independents used, namely leadership style, human relations, and work discipline. The population in this study were employees of the Department of Cooperatives and Micro Enterprises, Sumenep Regency. The sample in this study was taken as a whole. The data collection method used is the distribution of questionnaires to the respondents. The data analysis technique used is multiple linear regression. The results of the study stated that simultaneously the variables of leadership style, human relations, and work discipline had a significant effect on employee performance. While partially human relations have a significant effect on employee performance, but leadership style and work discipline have no significant effect on employee performance. Keywords: leadership style, human relations, work discipline and employee performance